Nomophobia in healthcare: an observational study between nurses and students: nursing students and nomophobia - Marletta, Giuseppe; Trani, Serena; Rotolo, Giulia; Di Monte, Maria Carmela; Sarli, Leopoldo; Artioli, Giovanna; La Torre, Pasquale; Pedrazzi, Giuseppe (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: The abuse of technical devices can be considered a form of addiction that is defined in current literature as Nomophobia. The phenomenon appears to be quite widespread among nurses and nursing students, and nomophobic behaviours of professionals can lead to a reduction in the quality of the care provided. The aim of this study is to investigate the situation in a University and in a hospital in northern Italy and evaluate the levels of nomophobia among nurses and students. Methods: An observational study was conducted with a questionnaire using a sample of nursing students and nurses. Both of the studies had the common goal of investigating the levels of nomophobia and evaluate the comparison between the two groups. Results: In general, neither nurses nor students seem to demonstrate nomophobia’s critical levels. The comparison of the daily use of the smartphone between nurses and students shows that the frequent use of students is balanced by the nurses’ daily trend line that progressively decreases. Both nurses and students affirm to use their smartphones at work with a certain frequency although, especially among the students, it is usually for appropriate and justified reasons. Conclusions: It is necessary to consider the development of an educational project that regulates the use of smartphones, explaining the meaning of nomophobia, right from the first year of the University experience so as to correctly address the students’ (and future professionals’) behaviours to make them aware of the misuse of mobile phones, especially in the clinical setting that can easily cause distractions and consequently irreversible errors.